Initial national priorities for comparative effectiveness research (National Academies Press, 2009)
"Clinical research presents health care providers with information on the natural history and clinical presentations of disease as well as diagnostic and treatment options. In today's healthcare system, patients, physicians, clinicians and family caregivers often lack the sufficient scientific data and evidence they need to determine the best course of treatment for the patients' medical conditions. Initial National Priorities for Comparative Effectiveness Research(CER) is designed to fill this knowledge gap by assisting patients and healthcare providers across diverse settings in making more informed decisions. In this 2009 report, the Institute of Medicine's Committee on Comparative Effectiveness Research Prioritization establishes a working definition of CER, develops a priority list of research topics, and identifies the necessary requirements to support a robust and sustainable CER enterprise. As part of the 2009 American Recovery and Reinvestment Act, Congress appropriated $1.1 billion in federal support of CER, reflecting legislators' belief that better decisions about the use of health care could improve the public's health and reduce the cost of care. The Committee on Comparative Effectiveness Research Prioritization was successful in preparing a list 100 top priority CER topics and 10 recommendations for best practices in the field."--Executive summary